1999
DOI: 10.1117/12.349547
|View full text |Cite
|
Sign up to set email alerts
|

<title>Fundamental information content accessible with medical x-ray scatter imaging</title>

Abstract: Although scattered radiation is generally regarded as a nuisance in radiological imaging, many innovative imaging concepts that use the scattered field have been demonstrated. A systematic approach, however, for analyzing the medical applications of x-ray scatter imaging has been lacking. We have therefore formulated a simple semi-analytic model that consists of imaging a target object against a background material of the same dimensions when both are situated within a water phantom. The target and background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…X-ray scatter imaging is a new approach to x-ray instrumentation for medicine. Several groups have been investigating ways to make use of scattered x-radiation to extend the usefulness of x-ray imaging beyond conventional primary beam imaging (Brateman et al 1984, Arendtsz and Hussein 1995, Leclair and Johns 1998, 1999, Poletti et al 2002, Davidson et al 2005, Leclair et al 2006, Van Uytven et al 2007, Griffiths et al 2007, Elshemey and Elsharkawy 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray scatter imaging is a new approach to x-ray instrumentation for medicine. Several groups have been investigating ways to make use of scattered x-radiation to extend the usefulness of x-ray imaging beyond conventional primary beam imaging (Brateman et al 1984, Arendtsz and Hussein 1995, Leclair and Johns 1998, 1999, Poletti et al 2002, Davidson et al 2005, Leclair et al 2006, Van Uytven et al 2007, Griffiths et al 2007, Elshemey and Elsharkawy 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in our group has analysed the improvement in image quality possible through using scattered x rays (Leclair and Johns 1998). As an example, it was shown that to distinguish between a 1 mm target of gray matter versus water, the signal-to-noise ratio can be multiplied by about 14 by using the coherently-scattered photons as compared to the primary (Leclair and Johns 1999). This analysis was based on the available data for the scattering properties of the tissues in question.…”
Section: Introductionmentioning
confidence: 99%
“…Results shown in Ref. 23, however, show that the general conclusions of Ref. 13 do not change if ⌿ 0 is fixed instead of ⌽ 0 .…”
Section: Model Of X-ray Scatter Imagingmentioning
confidence: 87%
“…A number of researchers have configured laboratory prototypes to demonstrate imaging using either backscatter (Towe andJacobs 1981, Herr et al 1994) or forward scatter (Harding et al 1985, Kleuker et al 1998, Westmore et al 1996, Batchelar and Cunningham 2002. We developed a semi-analytic model (Leclair and Johns 1998, 1999a, 1999b for analysing and comparing x-ray scatter imaging systems. Our calculations predict that for some imaging tasks, the contrast and signal-to-noise ratio achieved by collecting a portion of the scatter (in an annular cone) will be superior to that achieved by conventional primary imaging, for the same number of photons incident on the patient.…”
Section: Introductionmentioning
confidence: 99%